Factors that influence orgranization to engage with Ai-based tools - Amretjit, Singh Khalae (2023)
The research will be looking into the factors that influence organization to engage with AI-based tools. The beginning of the research will establish the background of how the progress of technology has been brought forward to the use of AI within organizational. The introduction of the research problem and the significance of the research. The next part of the research will establish of the dependent variable and independent variables are AI usage being dependent variable and the independent variable are organizational culture, financial performance and decision making. The research will be setting the hypothesis that will be tested. The research will be using a questionnaire using google from with the aim of gaining 120 respondents to receive a sufficient data to make conclusions and analysis. The analysis the research will be using inferential analysis and descriptive analysis to make a proper judgment of the findings. The research will use the data gained to conclude with a significant relationship between the independent variable and the dependent variable. The research will be assessing the impact of the research findings on the data and the discussion of the positive or negative relationship between the variables. The research will give the limitations that are present to gain a deeper understanding of the topic. There will even be a recommendation for future research to consider to enhance the capabilities of the finding of the data and analysis.